The duke not taken [large type] - London, Julia (London, Julia. Royal match, 2022)
"Ever since her sister became queen two years ago, Amelia Ivanosen, Princess of Wesloria, has been flirting and skirting scandal -- just barely. Before she does anything too outlandish, she is sent to England and Lila Aleksander, illustrious matchmaker to the ton, is recruited. Respectably ensconced at the country estate of a family friend, Amelia is introduced to many eligible bachelors, but . . . there is no spark. There never seems to be unless the man is completely wrong for her. Next door lives Joshua Parker, Duke of Marley, who is grumpy and reclusive -- for good reason. His first wife died in childbirth. When Marley is dragged by a friend to his neighbor's soiree, he and Amelia instantly dislike each other. Their banter is snarky and heated. He's a stuck-up smarty-pants; she's a self-involved, annoying princess. Sparks fly when they're together -- fireworks, actually -- but they loathe each other. Really. So why can't they stop thinking about each other?"--